Implementation of Risk Management in Murabahah Financing at BPRS in Aceh Province (International Journal of Scientific Research and Management (IJSRM), 2023)
This research aims to determine the extent of risk management is implemented in murabahah financing at BPRS in Aceh Province before and after the implementation of POJK No.23/POJK.03/2018. Before the POJK came into effect, BPRS did not have specific regulations regarding the implementation of risk management and were guided by the internal regulations of each BPRS, whereas after POJK No.23/POJK.03/2018 came into effect, BPRS were obliged to follow the regulations in this regulation, in this case the Financial Services Authority (OJK) regarding the implementation of risk management and must update the internal regulations of each BPRS to adapt to the POJK. This research uses primary data, namely information from interviews with parties who carry out risk management and documentation from the BPRS in Aceh Province. Methodology used is a qualitative descriptive research, and then collecting the data obtained then interpreting and analyzing it so that it can provide information that is used to solve the problems faced. The research results show that the application of risk management to murabahah financing at BPRS in Aceh Province before POJK No.23/POJK.03/2018 came into effect obtained the highest score is 94% and the lowest 61%. And Then after POJK No.23/POJK.03/2018 came into effect, there were significant changes with the highest average value being 100% and the lowest 80% assessed based on indicators in accordance with OJK provisions. The implications of implementing risk management for murabahah financing, if it is not implemented correctly, is the potential risk of financing problems and the level of BPRS soundness decreasing.